Current Advancements in Stereo Vision - Bhatti, Asim (IntechOpen, 2012)
The book is a new edition of stereo vision book series of INTECH Open Access Publisher and it presents diverse range of ideas and applications highlighting current research/technology trends and advances in the field of stereo vision. The topics covered in this book include fundamental theoretical aspects of robust stereo correspondence estimation, novel and robust algorithms, hardware implementation for fast execution and applications in wide range of disciplines. Particularly interesting approaches include neuromorphic engineering, probabilistic analysis and anisotropic reaction diffusion addressing the problem of stereo correspondence and the applications in mobile robotics for autonomous terrain mapping and navigation. SterCentre for Intelligent Systems Research (CISR), Institute of Technology, Research and Innovation (ITRI),eo algorithm with anisotropic reaction-diffusion systems utilizing biologically motivated reaction-diffusion systems with anisotropic diffusion coefficients makes it an interesting addition to the book.